Improving aftercare with technology for anorexia nervosa after intensive inpatient treatment: A pilot randomized controlled trial with a therapist‐guided smartphone app. Issue 10 (20th August 2019) - Neumayr, Christina; Voderholzer, Ulrich; Tregarthen, Jenna; Schlegl, Sandra
Abstract: Objective: To evaluate the feasibility, acceptability, and preliminary efficacy of an innovative therapist‐guided smartphone‐based aftercare intervention following inpatient treatment of patients with severe anorexia nervosa (AN). Method: Forty female patients with AN (ICD‐10: F50.0/F50.1) (aged: 15–36 years) were randomized either to an 8‐week smartphone‐based aftercare intervention (German version of "Recovery Record") with therapist feedback as an adjunct to treatment as usual (intervention group [IG]) or to treatment as usual alone (control group [CG]). Body mass index (BMI) and eating disorder (ED) symptoms were assessed at discharge (baseline), postintervention (after 8 weeks), and at 6‐month follow‐up. Additionally, patients' satisfaction, adherence to the smartphone‐based intervention, and postdischarge health care utilization were evaluated. Results: Patients showed a high level of adherence and reported a very high acceptance of the app and the aftercare intervention. We found at postintervention nonsignificant small to moderate between‐group effect sizes favoring the IG regarding BMI ( d = −0.24; 95% confidence interval [CI] [−0.90, 0.41]) and ED symptoms (Eating Disorder Examination‐Questionnaire global: d = 0.56; 95% CI [−0.10, 1.22]). At 6‐month follow‐up, effects wore off and no significant differences between the IG and CG were evident. Discussion: This was the first study to evaluate a therapist‐guided smartphone‐based aftercare intervention for discharged inpatients with AN. Results suggest that such an intervention is highly accepted by patients and that it could support symptom stabilization or continued improvement as an add‐on therapy to treatment as usual. A larger scale randomized controlled trial is now planned to further evaluate the efficacy of this aftercare intervention for patients with AN.